PERLINDUNGAN KONSUMEN ATAS IKLAN PRODUK ROKOK SEBAGAI UPAYA MENURUNKAN PREVALENSI PEROKOK ANAK - Tiara Nabila (Prodi Ilmu Hukum Fakultas Hukum Universitas Warmadewa, 2023)
The high prevalence of child smokers is partly due to the massive circulation of cigarette product advertisements in various media, be it in print, broadcasting, information technology, and/or outdoors, giving exposure to children who see it. This study aims to determine the view of the Indonesian Legislation on cigarette advertising and consumer protection efforts on cigarette product advertising in an effort to reduce the prevalence of child smokers. This research applies normative juridical method with secondary data obtained through literature study with primary legal materials in the form of UUPK, Broadcasting Law, Health Law, and PP No. 109/2012, secondary legal materials in the form of draft laws, research results, books, scientific articles, and scientific journals, as well as tertiary legal materials in the form of dictionaries, the collected data is analyzed using descriptive analysis techniques. Legal protection of child smokers as consumers in order to reduce the prevalence of child smoking has been regulated in regulations that contain control of cigarette product advertising, but the results of the study state that children can still access cigarette advertisements spread on social media, especially e-cigarette advertisements, while control of e-cigarettes has not been regulated in PP No.109/2012. In order for the protection of children from cigarette advertisements to run optimally, strict supervision by the government, authorities, and the community is needed to prohibit minors from accessing cigarette advertisements, conduct socialization in every school, and accelerate the revision of PP No. 109/2012.